The Study of Recycled Low-Density Polyethylene Reinforced Polyurethane Foam for Vehicle Interior Roof Headliner - HISHAM, MUHAMMAD SYAZWAN AIMAN; MARSI, NORAINI (Progress in Engineering Application and Technology, 2023)
This study explores the characteristics of Low-Density Polyethylene (LDPE) reinforced Polyurethane foam (PU) for vehicle interior roof headliners, as Polyethylene (PE) has limited suitability in the automotive industry due to its inadequate modulus and temperature resistance. This research seeks to develop environmentally friendly composite materials by exploring different composition ratios of LDPE reinforced PU namely 5, 10, 15, and 20 (wt/wt%), utilizing abundant waste resources like LDPE in Malaysia, with a specific focus on their suitability for vehicle interior roof headliners. Polyurethane (PU) foam was formed by combining polyol and isocyanates, while recycled low-density polyethylene (LDPE) was incorporated at varying ratios to create LDPE reinforced PU. The mechanical properties of the LDPE reinforced PU were assessed through Tensile tests (ASTM D638) and Impact tests (ASTM D256), and physical properties were examined using Density and Porosity tests (ASTM D792), Thermal analysis (Ansys Production), and Optical microscopic (OM) tests (ASTM F410). The sample with a ratio of 10 (wt/wt%) demonstrated the highest density (10 g/cm3), maximum porosity (0.34%), highest tensile strength (3.68 N/m2), an increase in temperature of 24.9 °C, and consistent foam structure and cellular form with increasing proportion of plastic waste particles. In summary, the findings indicate that the sample with a 10 (wt/wt%) ratio displayed the highest density, maximum porosity, and highest tensile strength. Moreover, the thermal analysis demonstrated a temperature increase, and the optical microscopic analysis confirmed a consistent foam structure with an increase in the plastic waste particle ratio. These results suggest the promising potential of LDPE reinforced PU foam as a suitable material for automotive applications.